Agribusiness embracing digital technology - Bisht, Sushma (Indian Farming, 2019)
Adoption of digital technologies in agriculture has been increasing at a rapid pace. Precision agriculture technologies are changing the way that farmers manage their crops and being adopted at a growing rate. Technology in agriculture, also known as AgTech has rapidly changed the industry. People in the industry—farmers, food producers—must embrace the digital transformation trends in agriculture. By using technology as a sustainable and scalable resource, we will be able to take agriculture to new heights. Internet of things (IoT) is simplifying and streamlining the collection, inspection and overall distributing of agricultural resources using sensors on equipment and materials. Robotics within agriculture would improve productivity and would result in higher and faster yields. Robots used for spraying and weeding can reduce agrochemical use incredibly. Most innovative pieces of the digital transformation is the ability to use machine learning and advanced analytics to mine data for trends. This can start way before the planting seed, with plant breeders. Machine learning can predict which traits and genes will be best for crop production, giving farmers all over the world the best breed for their location and climate. Machine learning algorithms can also be used within the manufacturing aspect of agriculture, where consumers purchase their products. Time is now that we really need to move with a sense of urgency to apply these new tools to accelerate the pace of agriculture development.